Kontribusi Ilmu Pengetahuan dan Teknologi (IPTEK) dalam Perkembangan Sistem Ekonomi Islam - Nur Fadilah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2019)
Abstract The development of the IPTEK (Science and Technology) world has brought tremendous benefits for the advancement of human civilization. The types of work that previously demanded considerable physical capability, are now relatively can be replaced by automatic machine devices. The working system that has been over-enabling human energy with the science and sophistication of technology is amazing. The civilization of the nation and the world society in the future is understood and realized will be faced with the complex situation in various branches of science. Therefore, to power, the IPTEK is required lofty values to be accountable. The debate that IPTEK's contributions with the development of an area the Islamic economic system is still ongoing. This is due to the absence of a theory, research, or model that can explain the relationship between the two factors above. It takes a test using a valid method to generate an accurate conclusion on the development and contribution of IPTEK applications with the development of the Islamic economic system. Nevertheless, some communities still believe that IPTEK's contributions to the development of the Islamic economic system of a particular region.